In Vitro Structure-Activity Relationship of Re-cyclized Octreotide Analogues - Dannoon, Shorouk F. (2010)
INTRODUCTION: Development of radiolabeled octreotide analogues is of interest for targeting somatostatin receptor-positive tumors for diagnostic and therapeutic purposes. We are investigating a direct labeling approach for incorporation of a Re ion into octreotide analogues, where the peptide sequences are cyclized via coordination to Re rather than through a disulfide bridge. METHODS: Various octreotide analogue sequences and coordination systems (e.g., S(2)N(2) and S(3)N) were synthesized and cyclized with non-radioactive Re. In vitro competitive binding assays with (111)In-DOTA-Tyr(3)-octreotide in AR42J rat pancreatic tumor cells yielded IC(50) values as a measure of somatostatin receptor affinity of the Re-cyclized analogues. Three-dimensional structures of Re-cyclized Tyr(3)-octreotate and its disulfide-bridged analogue were calculated from two-dimensional NMR experiments to visualize the effect of metal cyclization on the analogue’s pharmacophore. RESULTS: Only two of the eleven Re-cyclized analogues investigated showed moderate in vitro binding affinity toward somatostatin subtype 2 receptors. Three-dimensional molecular structures of Re- and disulfide-cyclized Tyr(3)-octreotate were calculated, and both of their pharmacophore turns appear to be very similar with minor differences due to metal coordination to the amide nitrogen of one of the pharmacophore amino acids. CONCLUSIONS: Various Re-cyclized analogues were developed and analogue 4 had moderate affinity toward somatostatin subtype 2 receptors. In vitro stable studies that are in progress showed stable radiometal-cyclization of octreotide analogues via NS(3) and N(2)S(2) coordination forming 5- and 6- membered chelate rings. In vivo biodistribution studies are underway of (99m) Tc- cyclized analogue 4.